Acute myeloid leukemia along with Gaucher disease in a child - Priyanka Maity,; Sudip Roy,; Rhituparna Das,; Moumita Sengupta,; Subham Bhattacharya, (Indian Journal of Case Reports, 2021)
There is sparse literature on the occurrence of acute leukemia in association with Gaucher disease in adults. Earlier, only two cases have been published describing acute leukemia in association with Gaucher disease in the pediatric age group. In this case report, we have described a case of acute myeloid leukemia along with Gaucher disease in an 8-year-old female child who presented with fever with hepatosplenomegaly. Measurement of ?-glucosidase activity was the key modality in diagnosis. The possibility that the reduction of the enzyme in Gaucher disease is related to the development of hematological malignancies needs to be explored.